Novel Phenotype in Unbalanced 7;9 Translocation with Critical Incidental Finding - Julie Fischer; Luis Rohena (Case Reports in Genetics)
This case discusses a now 13-year-old boy who underwent chromosome analysis and fluorescence in situ hybridization (FISH) for subtelomeric rearrangements due to dysmorphic features at birth. This testing revealed a diagnosis of an unbalanced 7;9 translocation resulting in monosomy for 7q34-qter and trisomy for 9pter-p21, which resulted in a very complex medical course. At the age of 12, due to persistent complex neurodevelopmental concerns, the patient was referred by neurology for whole-exome sequencing. This testing revealed an incidental pathogenic heterozygous KCNH2 deletion, which is associated with long QT-syndrome type II. Prior to this point, the patient had no symptoms of long QT syndrome and had multiple EKGs with normal QT intervals. However, due to this association, the patient underwent Holter monitoring, which revealed clinical evidence of long-QT syndrome type II. Preventative treatment was then initiated and the patient remains asymptomatic. This case expands on the phenotype of this patient’s unbalanced 7;9 translocation as well as highlights the importance of secondary findings in genetic testing.